Book Extract: "Laughter in the Dark: Egypt to the Tune of Change" by Yasmine El Rashidi - El Rashidi, Yasmine (New Agenda: South African Journal of Social and Economic Policy, 2024)
PRAISE FOR Laughter in the Dark “Laughter in the Dark is a brilliantly composed portrait of Egypt’s answer to hip-hop—and how it functions as a musical genre, economic engine, and cultural force amid the restrictions of an increasingly authoritarian regime. Meticulously reported and elegantly written, it’s a must-read for any global citizen.” –ZACK O’MALLEY GREENBURG, author of Empire State of Mind: How Jay-Z Went From Street Corner to Corner Office “In Laughter in the Dark, Yasmine El Rashidi provides a brisk, brilliant, and brave portrait of young Egyptians simmering under the weight of President Abdel Fattah El-Sisi’s repressive dictatorship and reveals the stark inequality between the rulers and the ruled.” –BASHARAT PEER, author of A Question of Order: India, Turkey, and the Return of Strongmen